Neuro-ophthalmologic and blood biomarker responses in ADHD following subconcussive head impacts: a case–control trial - Nowak, Madeleine K.; Kronenberger, William G.; Rettke, Devin; Ogbeide, Osamudiamen; Klemsz, Lillian M.; Quinn, Patrick D.; Mickleborough, Timothy D.; Newman, Sharlene D.; Kawata, Keisuke (Frontiers in Psychiatry, 2023)
Introduction This clinical trial aimed to determine the influence of attention-deficit/hyperactivity disorder (ADHD) on neuro-ophthalmologic function and brain-derived blood biomarkers following acute subconcussive head impacts. Methods The present trial consisted of age- and sex-matched samples with a ratio of 1:1 between two groups with a total sample size of 60 adults (age ± SD; 20.0 ± 1.8 years). Soccer players diagnosed with and medicated daily for ADHD were assigned into an ADHD group (n = 30). Soccer players without ADHD were assigned into a non-ADHD group (n = 30). Participants performed 10 soccer headers with a soccer ball projected at a velocity of 25mph. King-Devick test (KDT), near point of convergence (NPC), and serum levels of NF-L, tau, GFAP, and UCH-L1 were assessed at baseline (pre-heading) and at 2 h and 24 h post-heading. Results There were no statistically significant group-by-time interactions in outcome measures. However, at baseline, the ADHD group exhibited lower neuro-ophthalmologic functions compared to the non-ADHD group (NPC: p = 0.019; KDT: p = 0.018), and persisted at 2 h-post (NPC: p = 0.007; KDT: p = 0.014) and 24 h-post heading (NPC: p = 0.001). NPC significantly worsened over time in both groups compared to baseline [ADHD: 2 h-post, 1.23 cm, 95%CI:(0.77, 1.69), p < 0.001; 24 h-post, 1.68 cm, 95%CI:(1.22, 2.13), p = 0.001; Non-ADHD: 2 h-post, 0.96 cm, 95%CI:(0.50, 1.42), p < 0.001; 24 h-post, 1.09 cm, 95%CI:(0.63, 1.55), p < 0.001]. Conversely, improvements in KDT time compared to baseline occurred at 2 h-post in the non-ADHD group [−1.32 s, 95%CI:(−2.55, −0.09), p = 0.04] and at 24 h-post in both groups [ADHD: −4.66 s, 95%CI:(−5.89, −3.43), p < 0.001; Non-ADHD: −3.46 s, 95%CI:(−4.69, −2.23), p < 0.001)]. There were no group-by-time interactions for GFAP as both groups exhibited increased levels at 2 h-post [ADHD: 7.75 pg./mL, 95%CI:(1.41, 14.10), p = 0.019; Non-ADHD: 7.91 pg./mL, 95%CI:(1.71, 14.14), p = 0.015)] that returned to baseline at 24 h-post. NF-L levels increased at 2 h-post heading in the ADHD group [0.45 pg./mL, 95%CI:(0.05, 0.86), p = 0.032], but no significant NF-L changes were observed in the non-ADHD group over time. Discussion Ten soccer headers elevated GFAP levels and NPC impairment in both groups. However, persisting group difference in NPC, blunted KDT performance, and increased NF-L levels in the ADHD group suggest that ADHD may reduce neuro-ophthalmologic function and heighten axonal response to soccer headers. Clinical trial registration ClinicalTrials.gov, identifier ID: (NCT04880304).